Description of a new phlebotomine species (Diptera: Psychodidae, Phlebotominae) and new records of sand flies from the State of Acre, northern Brazil - Teles, Carolina Bioni Garcia; Freitas, Rui Alves; de Oliveira, Arley Faria José; Ogawa, Guilherme Maerschner; de Araújo, Edicarlos André Cavalcante; Medeiros, Jansen Fernandes; Pessoa, Felipe Arley Costa; Camargo, Luís Marcelo Aranha (Zootaxa, 2013)
Groundbreaking studies of phlebotomine sand fly populations in Assis Brasil, State of Acre, Brazil, resulted in the collec-tion of 13 new records of phlebotomine sand flies and one previously undescribed species. Lutzomyia naiffi sp. nov. is described here. The new species is similar to Lutzomyia columbiana (Ristorcelli & Van Ty) in measurements and other morphological characters.